Analysis of Guidance and Counseling Teacher Skills Using Self-Assessment Techniques - Anne Hafina (Universitas Pendidikan Indonesia (UPI), 2022)
This study aims to describe the counseling skills of counseling teachers. The urgency of counseling skills for counseling teachers to support professionalism in providing counseling services to counselees. A quantitative approach is carried out in research using survey methods through questionnaires to participants. The use of self-assessment techniques in answering the questionnaire was carried out to determine the participants' understanding of their skills. A total of 44 guidance counselors participated in the research from various districts/cities in West Java, Indonesia. The results showed that in general, counseling teachers were quite skilled (68%) in carrying out the basics of counseling. The four counseling skills analyzed are attending, responding, personalizing, and initiating.